Perpaduan Aspek Sosial-Budaya Melayu Dan Jawa Pada Kehidupan Ekonomi Masyarakat Nelayan Tradisional - Mahalizikri, Irawan Fakhrudin (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2016)
Boeke probably not the first to fully conduct studies on dimensional-culture in economic activity in rural communities traditional refer to as "community pre-capitalist" however, Boeke least to the author that brought us that how many and which various studies on economic, status, role, and meaning traditional village almost seriously neglected, and always placed as an "object" and not as "subjects". On the other hand, although in years past, studies sociological and anthropological have devoted much attention to the social life -economic archipelago, but only few who can focus studied on the patterns and practices of the economy which is managed and led by " natives "with other forms of relations and economic networks that are" internal ". In general, the pressure of their studies many put on intermediary Europeans than natives itself, as studies ever done by Geertz (1963), and Burger (1980) In this context, we need to give high appreciation of the work-classic of Van Leur ( 1967) and Schrieke (1955-1957), because the two of these studies who pioneered socioeconomic by trying to put out based on the meaning important people Asians (Indonesia) inactivity, channel, and the network economy (trade) world.if unfortunately, these studies mostly done in the days of pre-colonial and colonial.Study-study of the most important relationships and economic networks (trade) "local and regional" basically been started by Dewey in his "Pleasant Marketing inJava" (1962) and Geertz through his work "Peddlers and Princes" (1963). Both works scientific tries to connect the activities of traders and the general economic situation entrepreneurs within a society that is changing and extensively outlining its association with the socio-cultural context of the economic event concerned. Every lack of studies on aspects of socio-cultural in activity economic in this traditional rural communities also occurs in people ditch the village a new stream, particularly among the traditional villages in the coastal areas in Riau. Of the existing literature, these studies focus on many people’s lives "of traditional fishermen in coastal regions" (traditional peasant society), as wherewith done by Kuntowijoyo (1980); Leunissen (1982; 1989), Touwen-Bouwsma (1989a), Smith (1989) with a focus on social and economic life. While studies DeJonge (1977), Bouvier (1987) focuses on the study of life social-cultural, or a number of other studies of Kuntowijoyo (1980; 1993); Touwen-Bouwsma (1989b); de Jonge (1989b) on the socio-political aspects in the life people Madura; as well as with regard to religious life (Islam), whether committed by de Jonge (1989a), Kuntowijoyo (1989) and Akhmad Khusyairi (1989). Meanwhile research on the background of people’s lives shores relatively little, it was not completely regarding the activities of the fishermen in the field of marine fisheries, whereas although agriculture and gardener can be eye-main livelihood for most residents of Bengkalis islands, but marine fisheries besides having important meaning in the construction economy the local community, also used as a kind of "complementary" due to land in the islands on the island of Bengkalis and in accordance with studied Jonge (1989c), which states that in a statistical activity community economy coastal sector of marine fisheries is a sector of the economy the most important, after the agricultural sector and other research highly relevant to this study. From the studies that have been done in a number of papers as well as existing research as in other research Madura society, there are about 8% of the principal livelihood as a fisherman. The amount will be greater if the value with nearly equal numbers of those who make a living fishing occupation on a time basis. An amount, estimated at nearly a quarter of every fisherman in Java and Madura. Other researchers, such as Munir (1985) and Djojomartono (1985) focuses on the study of traditional rites surrounding death and birth of community Madurese fishermen. Study de Jonge, Munir and the Djojomartono, has provided an overview of even social activities, cultural, and economic background shares life community Madura. De Jong Studies have shown, although, how the economic activity of society (traditional or modern) can combine a reason sociological and cultural, in addition to economic factors own. It has also been shown by a number of other studies of Geertz (1956; 1963), Geertz (1981), McVey (1963), Wertheim (1959), Koentjaraningrat (1969, 1985), as well as Castles (1982), about a wide range of economic activity. The study was conducted in fishing traditional in desa selatbaru parit satu, dusun pantai indah, parit satu situated in the northern coastal region bordering the Malacca Strait, about 20 Km west of the town bengkalis on the island of Bengkalis or rather ± a four-hour drive from the city of the new week. The study was conducted for one month with approach qualitative and literature studies.